Pancreatic pseudocysts at unusual sites: A case report (Indian Journal of Case Reports, 2018)
A pseudocyst is a well-circumscribed fluid collection surrounded by a non-epithelialized wall of granulation tissue and fibrosis with no associated tissue necrosis that is present for 4 or more weeks after disease onset. Pseudocyst as a complication of acute pancreatitis can occur at any site in the abdomen and even in the mediastinum, but the intrahepatic location of a pancreatic pseudocyst is a very uncommon event. In the literature, only 36 such cases have been described. Computed tomography and high amylase levels obtained by the aspiration of the fluid play an important role in diagnosing this complication. There are no definite guidelines for the management of hepatic subcapsular pseudocyst. We present a case of a 32-year-old male who presented with acute pancreatitis, and radiological imaging was diagnosed with disrupted pancreatic duct and intrahepatic pancreatic pseudocyst in communication with a collection in the anterior abdominal wall.